Resilient Multi-Agent Systems Against Denial of Service Attacks via Adaptive and Activatable Network Layers - Deepalakshmi Babu Venkateswaran; Zhihua Qu (IEEE Open Journal of Control Systems)
This paper tackles the challenge of maintaining resilience in multi-agent systems under Denial of Service (DoS) attacks by proposing a robust architecture that includes an instantaneous detection algorithm for connectivity losses and a dynamic system to activate backup network layers when disruptions occur. We also introduce a simplified approach that reduces the number of required layers through an adaptive repair algorithm. The simulation section, divided into two parts, demonstrates the effectiveness of the algorithm: one part showcases its scalability in a large-scale system, and the other applies it to a real-world power system using the IEEE 123-node system. Both simulations confirm that the proposed approach significantly enhances system stability and performance under attack conditions.